THE PORTRAYAL OF A KOREAN ADOPTEE’S EXPERIENCE IN NICOLE CHUNG’S ALL YOU CAN EVER KNOW: A MEMOIR OF ADOPTION - Rizqia Nuur Maziyya (Universitas Gadjah Mada, 2021)
Transnational adoption has become one of the factors of transnational migration to Western countries, including America. Transnational adoption can be viewed from at least two perspectives, South Korea as the origin country and America as the targeted country. From the birth country, transnational adoption becomes a way to help the children from poverty, have a better future, and contribute to the birth country when they return. From the adoption-targeted country, this adoption is a humanitarian way to save the children from poverty, primitive way of life, and God’s blessing. One of the countries which regularly “send” the children to Western countries is South Korea. The children become Korean adoptees and mostly living in white American neighborhoods. Living with white Americans has shaped the Korean adoptees’ behavior and way of thinking same as Americans. Korean adoptees face various problems, starting from adjusting themselves in new environment, finding their cultural roots and identity, and struggling to find their biological parents. This study employed Phinnes’ ethnic identity development to make sense of the experience of a Korean adoptee called Nicole Chung in her memoir, All You Can Ever Know: A Memoir of Adoption. Through the discussion, it can be understood how transnational adoption programs become national agenda and big business field since it is not expensive to have children from other countries. There is also an assumption that the children will have better and happier life when they are taken to America and other western countries. However, throughout their life as adopted children in America, the children also find difficulties, especially in finding their identity.